2006
DOI: 10.1007/s11295-006-0060-2
|View full text |Cite
|
Sign up to set email alerts
|

Ecological impacts of trees with modified lignin

Abstract: Few experiments have yet been performed to explore the potential ecological impacts of genetic modification in long-lifespan species such as trees. In this paper, we review the available data on GM trees with modified lignin focussing on the results of the first long-term field trials of such trees. These trials evaluated poplars expressing antisense transgenes to reduce the expression of the lignin biosynthesis genes cinnamyl alcohol dehydrogenase (CAD) or caffeic acid/5-hydroxyferulic acid O-methyltransferas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 20 publications
1
33
0
Order By: Relevance
“…In respect of the numerous functions of lignin, there are various ways modified lignin might affect biological interactions, including effects on herbivory and defence responses against pathogens, decomposition of gm-material, and symbiotic interactions with mycorrhizal fungi (HALPIN et al, 2007). There are only a few reports on the ecological interactions of the lignin-modified trees in vivo (PILATE et al, 2002) or in vitro (TIIMONEN et al, 2005, SEPPÄNEN et al, 2007.…”
Section: Introductionmentioning
confidence: 99%
“…In respect of the numerous functions of lignin, there are various ways modified lignin might affect biological interactions, including effects on herbivory and defence responses against pathogens, decomposition of gm-material, and symbiotic interactions with mycorrhizal fungi (HALPIN et al, 2007). There are only a few reports on the ecological interactions of the lignin-modified trees in vivo (PILATE et al, 2002) or in vitro (TIIMONEN et al, 2005, SEPPÄNEN et al, 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these have been tested in field trials to determine if the improvements in saccharification rate, pulping, and forage properties observed in the GH trials were maintained during growth in the field . These trials suggest that lignin-modified plants are capable of attaining wild-type statures Halpin et al, 2007;Fornalé et al, 2011). In addition, these transformed plants have also been used to examine the consequences of lignin alteration for plant-soil, plant-insect, and plant-microbe interactions Tilston et al, 2004;Halpin et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Independent glasshouse (GH) and field studies were conducted with antisense CAD-and COMT-silenced poplar (Populus tremula 3 Populus alba; Pilate et al, 2002;Halpin et al, 2007) and CCR-and COMTsilenced (using an RNA interference [RNAi] strategy) perennial ryegrass (Lolium perenne; Tu et al, 2010) plants. These studies revealed that growth conditions had little impact on gene silencing efficiency and associated enzymatic activity, lignin content and chemistry, plant growth, and plant-insect or plant-microbe/ pathogen interactions.…”
mentioning
confidence: 99%
“…A number of economically important genes (Table 2) (for example, herbicide resistance, insect and disease resistance, reduced lignin, and growth traits) have been transferred to produce transgenic plants in several forest tree species. These include (1) herbicide resistance genes (aroA, BAR, CP4) in Populus (Fillatti et al 1987;Donahue et al 1994;Meilan et al 2002;Li et al 2008a, b), Eucalyptus (Harcourt et al 2000), Pinus radiata and Picea abies (Bishop-Hurley et al 2001;Charity et al 2005); (2) insect resistance gene (Bt) in Populus (Leple et al 1995;Wang et al 1996;Meilan et al 2000;Hu et al 1999;Yang et al 2003); Pinus radiata , Pinus taeda (Tang and Tian 2003) and Picea glauca (Lachance et al 2007); (3) bacterial and fungal resistance genes (D4E1, ChitIV, STS, ESF39A, ech42) in hybrid poplar (Populus tremula 9 P. alba) (Mentag et al 2003), in Betula (Pasonen et al 2004), in Populus , in Ulmus Americana (Newhouse et al 2007), and in Picea mariana and hybrid poplar (Populus nigra 9 P. maximowiczii) (Noël et al 2005); (4) stress tolerance gene (CaPF1) in Pinus strobus (Tang et al 2007) and salt tolerance gene (codA) in Eucalyptus (Yu et al 2009); and (5) lignin modification genes (CAD,4Cl,COMT,CAld5H) in Populus (Hu et al 1999;Pilate et al 2002;Baucher et al 2003;Li et al 2003;Halpin et al 2007;Hancock et al 2007) and Betula pendula (Tiimonen et al 2005). In most of these short-term studies there was a fairly stable and predicable expression of transgenes in the selected transgenic trees under greenhouse and confined field trials.…”
Section: Stability Of Transgene Expressionmentioning
confidence: 99%